Tidal effects on short-term mesozooplankton distribution in small channels of a temperate-turbid estuary, Southwestern Atlantic - Chazarretta, Javier (2015)
The short-term variability of mesozooplanktondistribution and physicochemical variables wasexamined in two different channels of the BahíaBlanca Estuary, Argentina, during two tidalcycles. All the physicochemical measurementsand mesozooplankton sampling were performedat a fixed site during approximately 22-23 h at3-h intervals. Pumps were used to obtain surfaceand bottom mesozooplankton samples and thewater speed of each stratum was measured withan Acoustic Doppler Current Profiler (ADCP). Inall, 23 mesozooplanktonic taxa belonging to fourphyla (Arthropoda, Annelida, Echinodermata andChordata) were identified. The most abundant taxaduring the two tidal cycles were Balanus glandulalarvae, Eurytemora americana and Acartia tonsa.A discernible variability in the water conditionsand vertical mesozooplankton distribution (VMD)different from that known for the estuary´s mainchannel, was found in the other two selectedchannels. VMD varied during the tidal cycle inboth channels in accordance with the channel?sgeomorphology and water dynamic characteristicsof each of them. The variation of the abundance ofthe different taxa during ebb and flood currents mightindicate the existence of a tidal vertical migrationof the mesozooplankton as a response to particulardynamic water conditions.